2002
DOI: 10.1055/s-2002-36516
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Involvement in Sarcoidosis

Abstract: Cardiac sarcoidosis is a challenging diagnostic entity. Manifestations range from an incidentally discovered, benign condition to fatal cardiomyopathy and arrhythmias. In this review, we discuss the salient clinical features, diagnostic evaluation, treatment, and prognosis of cardiac sarcoidosis. A definitive histologic diagnosis of myocardial sarcoidosis is difficult, and treatment may be necessary in some patients with suspected cardiac involvement even in the absence of histologic confirmation. Optimal stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
0
16

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 90 publications
(289 reference statements)
2
28
0
16
Order By: Relevance
“…Additionally, serious cardiac dysfunction has also been seen in 5-10% of sarcoidosis patients [Newman et al, 1997]. Overall our findings appear to be consistent with previous studies [Newman et al, 1997;Deng et al, 2002;Crystal, 2004;Smedema et al, 2007]. The incidence rates reported in this study would doubled if the additional 39 cases of sarcoid like granulomatous disease as seen in Figure 1 with incomplete medical records or a final diagnosis of granulomatous disease of unknown etiology were included in our study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Additionally, serious cardiac dysfunction has also been seen in 5-10% of sarcoidosis patients [Newman et al, 1997]. Overall our findings appear to be consistent with previous studies [Newman et al, 1997;Deng et al, 2002;Crystal, 2004;Smedema et al, 2007]. The incidence rates reported in this study would doubled if the additional 39 cases of sarcoid like granulomatous disease as seen in Figure 1 with incomplete medical records or a final diagnosis of granulomatous disease of unknown etiology were included in our study.…”
Section: Discussionsupporting
confidence: 91%
“…It has been mentioned in literature that joint involvement is more common than bone and muscle involvement and is seen in about 25-50% of sarcoidosis cases [Crystal, 2004]. Similarly, although clinical evidence of sarcoidosis affecting the heart is uncommon it has been seen in 2-7% of sarcoidosis patients [Deng et al, 2002;Smedema et al, 2007]. Additionally, serious cardiac dysfunction has also been seen in 5-10% of sarcoidosis patients [Newman et al, 1997].…”
Section: Discussionmentioning
confidence: 99%
“…Infiltration and resulting damage of the myocardium are important causes of death (2). Although autopsy studies have established that cardiac involvement is demonstrated in 20% to 50% of cases, cardiac sarcoidosis is symptomatic in only 5% of pa-tients, is an independent predictor of mortality and carries a very poor prognosis (3,4). Although cardiac sarcoidosis entails significant morbidity and mortality due to the development of fatal arrhythmia, atrioventricular conduction disturbances, and refractory congestive heart failure, it is not always easy to diagnose.…”
Section: Discussionmentioning
confidence: 99%
“…2 In patients with definite biopsy-proven or clinically-proven cardiac sarcoidosis (CS), corticosteroid therapy should be recommended, even if myocardial biopsy results are negative. 1,3 On the basis of this recommendation, a novel diagnostic approach has been challenged for earlier detection and assessment of cardiac involvement in sarcoidosis patients.…”
mentioning
confidence: 99%